The Effect of Self-Efficacy And Perceived Organizational Support On Readiness To Change In History Teachers - Christian Lisnawaty Situmorang; Tarmidi; Fillia Dina (Institute of Educational, Research, and Community Service, 2024)
Readiness to change for teachers is influenced by self-efficacy and perceived organizational support in carrying out the role of a teacher at school. Teachers who are always ready to face changes implemented in schools by increasing self-efficacy and perceived organizational support have an impact on increasing readiness to change. However, the opposite is found in history teachers who are members of MGMP (Musyawarah Guru Mata Pelajaran) Medan City. Readiness to change History teachers can still not deal with changes due to a lack of self-efficacy and perceived organizational support. With an increase in self-efficacy and perceived organizational support, it can increase teachers' readiness to change in schools. This study has a population of history teachers in Medan City with a purposive sampling technique of history teachers who are members of the Medan City MGMP. Data were collected using the readiness to change scale, self-efficacy scale, and perceived organizational support scale. Then the data were collected and analyzed by multiple linear regression using SPSS software. The results showed that self-efficacy and perceived organizational support significantly positively affect teachers' readiness to change.